A case report of AQP4-IgG-seropositive refractory neuromyelitis optica spectrum disorder patient with Sjögren’s syndrome and pancytopenia treated with inebilizumab - Li, Shasha; Gao, Yuting; He, Yang; Zhang, Zhaoxu (Frontiers in Neurology, 2024)
Patients with neuromyelitis optica spectrum disorder (NMOSD) coexisting with both Sjögren’s syndrome (SS) and pancytopenia are exceptionally rare. There is no study on the treatment of such patients. We presented a case of AQP4-IgG seropositive refractory NMOSD patient combined with SS and pancytopenia with significant response to inebilizumab. In 2017 the 49-year-old female patient was diagnosed with SS and pancytopenia without any treatment. In August 2022, she had a sudden onset of lower limbs weakness, manifested as inability to walk, accompanied by urinary incontinence. After receiving methylprednisolone and cyclophosphamide, she regained the ability to walk. In February 2023, she suffered from weakness of both lower limbs again and paralyzed in bed, accompanied by retention of urine and stool, and loss of vision in both eyes. After receiving methylprednisolone and three plasmapheresis, the condition did not further worsen, but there was no remission. In March 2023, the patient was admitted to our hospital and was formally diagnosed with AQP4-IgG seropositive NMOSD combined with SS and pancytopenia. After receiving two 300 mg injections of inebilizumab, not only the symptoms of NMOSD improved significantly, but also the symptoms of concurrent SS and pancytopenia. In the cases of AQP4-IgG seropositive NMOSD who have recurrent episodes and are comorbid with other autoimmune disorders, inebilizumab may be a good choice.